Methods to reduce risk in implementing investment projects in nuclear power plants (Путеводитель предпринимателя)
The main tasks ofthe Russian energy industry are considered, the specific features ofquality management to reduce risks of nuclear power plants are analyzed, methods to account for risk when calculating the efficiency of investment projects are suggested.